Evaluation of the effectiveness of telaga-based rainwater harvesting in arid regions - Utama, Tribudi; Bisri, Mohammad; Prayogo, Tri Budi; Haribowo, Riyanto; Limantara, Lily Montarcih (Journal of Water and Land Development, 2026)
This study evaluates the effectiveness of telaga-based rainwater harvesting (RWH) systems in Tepus and Semanu Sub-districts of Gunungkidul, Yogyakarta, Indonesia, in supporting water availability throughout the dry season. The methods included field surveys of 40 telaga/embung1 (morphometric/depth measurements, inlet– catchment conditions, and operational status), descriptive statistical analysis, and estimation of water losses using the FAO-56 Penman–Monteith method (ETo), which was converted into open-water evaporation (Eo). Results show an average designed storage volume of 14,870 m3, while actual effective volume is only approx. 35% due to an average sedimentation rate of 48.25% (50% of telaga fall into the ≥51% sedimentation category). The theoretical rainwater- harvesting effectiveness is 20.85%, whereas actual effectiveness is 6.09% (actual range 0–33.8%; 37.5% of telaga have lost their function). At peak dry-season conditions, Eo ranges from approx. 5–7 mm per day (approx. 31–43 m3 per day for an average surface area of 6,138 m2). Accumulated evaporation over approximately 90 days is equivalent to approx. 2.76–3.87∙103 m3, or approx. 53–74% of the initial effective storage (approx. 5.20∙103 m3). Operationally, telaga retain their functional capacity for only ±2–3 months after the rainy season, rendering their supply insufficient to meet demand over the entire dry period.